2020
DOI: 10.1038/s41419-020-02780-8
|View full text |Cite
|
Sign up to set email alerts
|

Dianhydrogalactitol synergizes with topoisomerase poisons to overcome DNA repair activity in tumor cells

Abstract: 1,2:5,6-Dianhydrogalactitol (DAG) is a bi-functional DNA-targeting agent currently in phase II clinical trial for treatment of temozolomide-resistant glioblastoma (GBM). In the present study, we investigated the cytotoxic activity of DAG alone or in combination with common chemotherapy agents in GBM and prostate cancer (PCa) cells, and determined the impact of DNA repair pathways on DAG-induced cytotoxicity. We found that DAG produced replication-dependent DNA lesions decorated with RPA32, RAD51, and γH2AX foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Phosphorylated histone variant H2AX (γH2AX) is a surrogate marker for DSBs in DNA (37). Dianhydrogalactitol (DAG) was included as a positive control because previous Ramos et al Manuscript studies in our group showed that DAG induces replication-dependent DNA damage in a variety of cancer cell lines (38,39). Treatment with kt-3283, olaparib or vorinostat induced γH2AX expression in a dose-dependent manner in both CHLA10 and TC32 cells.…”
Section: Kt-3283 Treatment Induces Dna Damage In Ewing Sarcoma Cellsmentioning
confidence: 99%
“…Phosphorylated histone variant H2AX (γH2AX) is a surrogate marker for DSBs in DNA (37). Dianhydrogalactitol (DAG) was included as a positive control because previous Ramos et al Manuscript studies in our group showed that DAG induces replication-dependent DNA damage in a variety of cancer cell lines (38,39). Treatment with kt-3283, olaparib or vorinostat induced γH2AX expression in a dose-dependent manner in both CHLA10 and TC32 cells.…”
Section: Kt-3283 Treatment Induces Dna Damage In Ewing Sarcoma Cellsmentioning
confidence: 99%